A low conversion loss single balanced subharmonic mixer. Issue 5 (24th January 2020) - Kumari, Sadhana; Mondal, Priyanka
Abstract: A new circuit topology for the design of a single balanced second‐order subharmonic mixer (SHM) is proposed. In the proposed topology, it is not necessary for the radio frequency (RF) and local oscillator (LO) signal to be within 15% frequency difference. Thus, the limitation of a conventional rat‐race mixer has been alleviated. Moreover, it shows very low conversion loss, high LO‐to‐RF, LO to intermediate frequency (IF), and 2LO‐to‐RF port isolations. The measured minimum down conversion loss is 5.8 dB at 13 GHz and remains below 7.65 dB over the 2 GHz RF operational band 12‐14 GHz for a fixed IF of 550 MHz. Measured LO‐to‐RF and LO‐to‐IF port isolations are better than −40 dB over the entire operational band. The 2LO‐to‐RF isolation is more than −62 dB which is extremely necessary for a second harmonic mixer where 2LO and RF frequency are close to each other. The input 1‐dB compression point is measured to be −1 dBm.